Cancer and Complementary Therapies: Current Trends in Survivors' Interest and Use. (September 2018) - Qureshi, Maryam; Zelinski, Erin; Carlson, Linda E.
Background. Cancer survivors use complementary therapies (CTs) for a variety of reasons; however, with interest and use reportedly on the rise and a widening range of products and practices available, there is a need to establish trends in and drivers of interest. We aimed to determine (1) frequencies of use, level of interest, and barriers for 30 specific CTs and (2) whether physical symptoms, perceived stress (PS), or spiritual well-being were related to interest levels. Method. A total of 212 cancer outpatients were surveyed at the Tom Baker Cancer Centre in Calgary, Canada. Results. Overall, up to 75% of survivors already used some form of CTs since their diagnosis. The most highly used were the following: vitamins B12 and D, multivitamins, calcium, and breathing and relaxation exercises. Those who had not used CTs indicated highest interest in massage, vitamin B12, breathing and relaxation, mindfulness-based stress reduction, and antioxidants. The most frequently reported barriers for all CTs were not knowing enough about what a therapy was and not having enough evidence on whether it worked. High PS predicted higher interest for all CTs, but spirituality was not significantly related to any. Physical symptoms, anxiety, and depression were significant predictors of interest for some CTs. Conclusion. These findings provide a blueprint for future clinical efficacy trials and highlight the need for clinical practice guidelines.